IMPACT OF CORPORATE OWNERSHIP CONTROL AGAINST COMPANY VALUE - Iskandar Zulkarnain; Riyanti; Sampor Ali; Erika Angelina (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This research is expected to improve theories related to company value. Jensen and Meckling (Jensen and Meckling) point out that agency theory is a theory of unequal interests between the party granting the authorization (principal), i.e. the investor, and the party receiving the authorization (agent), that is, the manager. As a company manager, the manager is accountable to the owner, which will affect the funds of the investor's or creditor's company. This research uses a quantitative approach. The main data needed is secondary data derived from the company's Annual report within 6 years, namely from 2015-2020 obtained from IDX or the website of each company The research population is 30 companies listed on the IDX data collected using the documentation method. The results showed that, that Ho was accepted and Ha was rejected, meaning that the Institutional Ownership variable had no effect and was not significant to the value of the company. Then Ho is accepted and Ha is rejected, meaning that the Concentrated Ownership variable has a positive and significant effect on the value of the company. And there is an influence of Institutional Ownership and Concentrated Ownership together as having a significant effect on the value of the company.